2012
DOI: 10.1371/journal.pone.0037803
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of SIK3 in Glucose and Lipid Homeostasis in Mice

Abstract: Salt-inducible kinase 3 (SIK3), an AMP-activated protein kinase-related kinase, is induced in the murine liver after the consumption of a diet rich in fat, sucrose, and cholesterol. To examine whether SIK3 can modulate glucose and lipid metabolism in the liver, we analyzed phenotypes of SIK3-deficent mice. Sik3 −/− mice have a malnourished the phenotype (i.e., lipodystrophy, hypolipidemia, hypoglycemia, and hyper-insulin sensitivity) accompanied by cholestasis and cholelithiasis. The hypoglycemic and hyper-ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(87 citation statements)
references
References 60 publications
2
84
0
1
Order By: Relevance
“…SIK3-KO mice display a lean phenotype, resistance to a high fat diet, and excessive hypoglycemia. Although a response to insulin and lactate-induced gluconeogenesis in SIK3-KO mice appeared to be normal under fasting conditions, gluconeogenic gene expression was extremely higher in the SIK3-KO liver than in WT mice (18). In addition to the lean phenotype (small amount of energy storage), impaired bile acid, cholesterol, and retinoid homeostasis with skeletal abnormalities in SIK3-KO mice (19) can make it difficult to determine whether enhanced gluconeogenic programs in the SIK3-KO mice liver were the results of a cell autonomous action or systemic effects.…”
Section: Salt-inducible Kinase (Sik)mentioning
confidence: 87%
See 3 more Smart Citations
“…SIK3-KO mice display a lean phenotype, resistance to a high fat diet, and excessive hypoglycemia. Although a response to insulin and lactate-induced gluconeogenesis in SIK3-KO mice appeared to be normal under fasting conditions, gluconeogenic gene expression was extremely higher in the SIK3-KO liver than in WT mice (18). In addition to the lean phenotype (small amount of energy storage), impaired bile acid, cholesterol, and retinoid homeostasis with skeletal abnormalities in SIK3-KO mice (19) can make it difficult to determine whether enhanced gluconeogenic programs in the SIK3-KO mice liver were the results of a cell autonomous action or systemic effects.…”
Section: Salt-inducible Kinase (Sik)mentioning
confidence: 87%
“…However, in vivo, we observed that only SIK3-KO mice had dramatic phenotypes for energy metabolism (18). To confirm the indispensability of SIK3 in glucose metabolism in vivo, all SIKs KO mice with the same genetic background (C57BL/6J) were subjected to a glucose challenge after 4 h of starvation (Fig.…”
Section: Gluconeogenic Program Is Constitutively Up-regulated In Sik3mentioning
confidence: 88%
See 2 more Smart Citations
“…To date, 12 kinds of AMPK‐RKs have been identified through their sequence homology with the protein kinase domain of AMPK, and eight kinds of kinases have been identified as distant relatives of AMPK 25. Some of them, such as SIK1, SIK2, and SIK3, were reported to regulate lipid metabolism 26, 27, 28. From these facts, we assumed that one or more AMPK‐RKs regulate the activity by which RBV suppresses lipogenesis.…”
Section: Resultsmentioning
confidence: 99%